Chiroptical amplification beyond enantiopurity in chiral films - Panagiotopoulou, Charitini; Liu, Shangpu; Pittrich, Johannes; Iglev, Hristo; Deschler, Felix; Kartouzian, Aras (Advanced optical materials, 2025)
Chiral films are key functional materials for spintronics, enantioselective sensing, and chiral photonics. Understanding and controlling chiroptical activity in such materials is crucial for advancing next-generation photonic and spintronic technologies. A widely held belief is that enantiopure systems inherently offer the strongest chiroptical responses. In this perspective, this assumption is questioned by drawing attention to nonlinear dependencies between normalized chiroptical response as given by the anisotropy factor, g, and enantiomeric excess (ee) in thin-film systems. Using 2D and 1D chiral hybrid metal-halide perovskites as testbeds, it is shown that the highest optical activity often emerges at intermediate ee values - far from the enantiopure limit. Also, for tryptophan (a chiral amino acid), a similar response is observed. This behavior points to complex structural reorganizations and interaction patterns in chiral films. The common practice of limiting chiroptical measurements on chiral films to racemic and enantiopure samples overlooks a rich, informative regime is believed. Systematic g-ee profiling is proposed as a standard part of the experimental workflow in chiral materials research, which can reveal underexplored material spaces and enable more deliberate control of chiroptical properties.